Етнолингвистические процессы на территории Восточной Прибалтики по данным археологии и смежных наук - Долуханов, Павел Маркович (Baltistica, 1989)
ETHNOLINGUISTIC PROCESSES IN THE EASTERN PERIBALTIC AREA AS BASED ON THE EVIDENCE OF ARCHAEOLOGY AND RELATED DISCIPLINESThe reconstruction of ethnolinguistic processes is possible based on correlating archaeological evidence with those of comparative linguistics and physical anthropology, taking into account the palaeoenvironmental data. One may distinguish two major concentration zones of the Upper Palaeolithic sites in Europe and in the Mediterranean basin; the first being tentatively attributed to the Uralian proto-languages, the second to the Basque-Caucasian group. The initial settlement of the eastern Peribaltic area occurred in the Late-Glacial period (13–10 t. y. b. p.) mostly from the first (Uralian) zone with a limited participation of elements stemming from the second zone. The proliferationfof the Indo-European languages is seen as resulting from the spread of the farming economy in the course of the 8th–6th millennia B. C. The initial penetration of the I. E. languages into the Eastern Peribaltic area is archaeologically reflected in the Narvian culture (4th–3rd millennia B. C). The Sperlings, Upper Volga and Volga–Kama cultures are seen as belonging to the Finno–Ugrian linguistic groups. The spread of the pit-and-comb decorated pottery within the forest zone in the 3rd millennium B. C. is considered as resulting from the cultural consolidation of Finno-Ugrian speaking communities. The Corded Ware cultures in the Middle and North-Eastern Europe (3rd–2nd millennia B. C.) are interpreted as belonging to undifferentiated German–Slavic–Baltic communities. In the course of the 1st millennium B. C. the predominantly Slavic-speaking communities established themselves in the forest-steppe zone (‘agricultural Scyths’) while Baltic-speaking communities dominated the Upper Dniepr and Danube basins, as well as the south-eastern Peribaltic areas.